2003
DOI: 10.1046/j.1439-0396.2003.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary oregano oil and α‐tocopheryl acetate supplementation on iron‐induced lipid oxidation of turkey breast, thigh, liver and heart tissues

Abstract: Twenty-five 12-week-old turkeys randomly divided into five groups were given a basal diet, or a basal diet supplemented with 200 mg alpha-tocopheryl acetate/kg, or 100 mg oregano oil/kg or 200 mg oregano oil/kg, or 100 mg oregano oil plus 100 mg alpha-tocopheryl acetate/kg diet, for 4 weeks prior to slaughter. Breast, thigh, liver and heart tissues were subjected to iron-induced lipid oxidation, the extent of which was determined by third-order derivative spectrophotometry. Results showed that dietary oregano … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 39 publications
(49 reference statements)
4
49
0
5
Order By: Relevance
“…An analogous lipid oxidative profile was observed when chicken meat was refrigerated stored at 4 o C for 9 days. These results are in agreement with recent studies showing that diet supplementation with oregano essential oil has the potential to increase the oxidative stability of chicken (Botsoglou et al, 2002a(Botsoglou et al, ,b, 2003a and turkey (Botsoglou et al, 2003b,c;Papageorgiou et al, 2003) tissues.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…An analogous lipid oxidative profile was observed when chicken meat was refrigerated stored at 4 o C for 9 days. These results are in agreement with recent studies showing that diet supplementation with oregano essential oil has the potential to increase the oxidative stability of chicken (Botsoglou et al, 2002a(Botsoglou et al, ,b, 2003a and turkey (Botsoglou et al, 2003b,c;Papageorgiou et al, 2003) tissues.…”
Section: Discussionsupporting
confidence: 92%
“…Alcicek et al (2003) also reported that dietary supplementation of an essential oil combination from 6 herbs including oregano improved chicken performance. However, other pertinent studies showed that supplementation of poultry diets with oregano essential oil at levels of 50 and 100 mg/kg for broilers (Botsoglou et al, 2002a), and at levels of 100 and 200 mg/kg for turkeys (Papageorgiou et al, 2003), had no beneficial effect on growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…In relevance to animal nutrition, most in vivo studies have been made on the antioxidant activity of oregano active components, showing improvement of the antioxidative stability of animal tissues during storage Papageorgiou et al, 2003;Janz et al, 2007). In our study, a significantly higher concentration of MDA, a marker commonly used to determine lipid peroxidation in biological samples, was found in the plasma and urine of pigs fed with the linseed oil.…”
Section: Discussionsupporting
confidence: 50%
“…Several studies have been conducted on the effect of dietary essential oils or combinations on the performance of poultry but with varying and often conflicting results. While some reports suggested that dietary herbal essential oils improved growth performance (Alcicek et al, 2003;Basmacioglou et al, 2004), others showed no such effect (Botsoglou et al, 2002a;Lee et al, 2003;Papageorgiou et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of poultry diets with essential oils has been found to be a simple and convenient strategy to introduce natural antioxidants into meat (Botsoglou et al, 2002a). In vivo studies have shown that oleoresins of rosemary and sage (Lopez-Bote et al, 1998), tea extracts (Tang et al, 2000; and essential oil of oregano (Botsoglou et al, 2002b;2003a,b,c;Papageorgiou et al, 2003) could increase the oxidative stability of chicken and turkey tissues when incorporated into their diets.…”
Section: Introductionmentioning
confidence: 99%